“Characterization of Blue Ballpoint Pens Using UV-Visible Spectroscopy and Pattern Recognition Techniques” - Bahman, Nur Atiqah Salwa (Universiti Sains Malaysia, 2015)
Analysis of ink is important particularly in the investigation of forgery cases involving handwriting and signatures. Characterisation of ballpoint pen inks among different brands becomes of great interest in questioned document since most of documents are written using ballpoint pens. The purpose of this study was to evaluate the possibility of discriminating 24 blue ballpoint pen inks from four different brands namely Kilometrico, G’Soft, Faber Castell and Stabilo. The blue ballpoint pen inks components were first separated using Thin Layer Chromatography (TLC) before the ink extracts were subjected to UltraViolet-Visible (UV-Vis) spectroscopy. The colour of the spots developed on the TLC plate and their Rf values as well as the UV-Vis spectra were examined manually by direct visual examination in attempt to classify the ink into their respective group. However, this approach had failed to differentiate the ink. The UV-Vis spectra of the ink which could not be differentiated were introduced to chemometrics techniques of Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). PCA had successfully differentiated and grouped all the blue ballpoint pen inks according to their brands manifested in the score plot. Using the Euclidean distance as the proximity measure and complete linkage as the linkage strategy to link cluster, HCA had also successfully differentiate the blue ballpoint pen inks under study according to the brand. The results proved that the UV-Vis spectra combine with chemometrics technique of PCA and HCA can be effective tool to differentiate blue ballpoint pen inks of different brands